Bohr’s inequality for analytic functions with hyperbolic range - Yusuf Abu Muhanna; Issam Louhichi (Mathematics Open, 2025)
In this paper, we use properties of the hyperbolic metric and the modular function to show that Bohr’s radius for covering maps onto hyperbolic domains is [Formula: see text] This includes almost all known classes of analytic functions.